Flesh & Foil - Roduit, Johann (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2016)
This poem reflects on the possibility of human enhancement. It shows that if enhancements are embraced step-by-step, without any long-term vision, one might get lost along the way.